Giant aneurysm of membranous septum. Unusual cause of mediastinal mass. Issue 1 (July 1981) - Sethia, B; Cotter, L
Abstract : A case of giant aneurysm of the membranous interventricular septum which presented as a mediastinal mass is described. Aneurysms of the membranous septum are rare and usually found incidental to the main cause of the patient's complaints. They are most commonly associated with ventricular septal defects but can also be found in the presence of ventriculoarterial discordance, atrioventricular canal defects, and semilunar valve abnormalities. In patients presenting with a mediastinal mass which may be cardiac, full left and right heart catheterisation are necessary; a simple right heart study is inadequate.